Pertumbuhan dan Variasi Jumlah Kromosom Akar Rambut Morus macroura Miq. Hasil Transformasi dengan Beberapa Galur Agrobacterium - Ermayanti, Tri Muji; Hastuti, Dwi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
Morus macroura Miq. (Moraceae) which is native West Sumatra is now classified as endangered species and usually used as furniture. This plant produces phenolic compounds. Generally secondary metabolites produced by plants are found in low level, therefore, in vitro techniques such as callus culture, cell suspension and organ cultures are the alternative methods to increase their in vitro production. However, problems on genetic instability such as variation in chromosome numbers and abnormality of chromosome structure are found. These cases influence the productions of secondary metabolites. Genetic variation could be overcome using hairy root culture. The aim of the research was to analyze the growth and chromosome numbers of Morus macroura Miq. hairy root transformed with Agrobacterium strains TISTR-511, TISTR-512, ATCC-15834 and R-1000 in order to determine the genetic variation of the culture. Growth was determined by measuring the fresh and dry weights of roots after 4 weeks in culture. Chromosome numbers was prepared by squashing. The results showed that transformed roots had higher growth compared to the growth of untransformed roots. The growth of hairy roots was varied depending on the strains of Agrobacterium. Both transformed and untransformed roots had high variation in the chromosome numbers. Genetic stability of both transformed and untransformed roots were low but they had similar pattern of distribution on the chromosome number. The roots had the diploid number of chromosome 2n=2x=28 ranged from 35.83 to 46.13% and the tetraploid numbers 2n=4x=56 ranged from 23.23 to 42.21%. Total cells examined were more that 230 cells.